Fostering Collaborative Edge Service Provision in Community Clouds with Docker - Baig, Roger; Freitag, Felix; Navarro, Leandro (2016 IEEE International Conference on Computer and Information Technology (CIT), 2016)
Cloud services are typically built by relying on computing resources and service available from major commercial providers. While these resources provided from large data centers will remain suitable for many types of services, the fog or edge cloud computing paradigm has been proposed for new types of services, which need the cloud computing infrastructure close to the network edge, even at the user premises. Nonetheless, in these approaches where the cloud infrastructure is pushed closer to the user, control over what services are offered remains at the choice of the operator, often subject to commercial decisions, keeping thus the scope of edge services below their true potential. In this paper we present a collaborative edge cloud deployment, which has been operational for more than a year, and its current evolution using Docker containers for service provision. We show how with the adopted container approach this community cloud enables the user to create and share services at the network edge. In our model the user can contribute services and computing resources, either for personal use or shared and even to support third-party services. As a consequence, more tailored and customized services can appear at the network edge, fitting better to fulfill specific local needs and constraints. While we show a concrete case in more detail to demonstrate our approach, its generalization has the potential to unleash the proliferation of cloud service provision at the network edge.